Good library software as prerequisite for quality information supply - Mrklic, Zoran; Vrana, Radovan (2001)
Time we live in is strongly influenced by use of IT in all spheres of our lives. Libraries as one of the most important institutions in society are no expection from this rule since their information services are improved and enhanced by use of IT. By mentioning library information services we are introducing their basic function: access to information. And how is this access possible today? It is more and more dependent on different hardware and software which helps librarians to keep information flow going from their collections to library users. Moreover, realization of this basic library function has always been depending on ocurrance of new media on which libraries kept stored human knowledge. Methods and procedures changed, need for information remained permanent. When we speak about needs for information we have to mention library software as one of the main access points to the stored human knowledge today. Having quality information system in library means following procedures and methods of information system development accompanied by the theory of library and information science i.e. knowledge organization.
Projekt MZOS
ENG